Gender-Based Comparative Study of the Influence of Cola Nitida on the Sweat Calcium and Magnesium Concentrations of Humans (Multitech Journal of Applied Sciences (MJAS), 2025)
The study examined how Cola nitida consumption influences sweat calcium and magnesium concentrations in male subjects compared to their female counterparts. A total of sixty participants (30 males and 30 females) with no prior habit of consuming Cola nut were included, all aged between 18 and 28 years. They were categorized into three sub-groups: underweight (10), normal weight (10), and overweight (10). Individuals with hypertension, renal issues, or cardio-pulmonary conditions were excluded from the study. Experiments were conducted under three conditions: normal chamber temperature (RT = 27°C, RH = 70%), raised chamber temperature (RT = 37°C, RH = 90%), and normal chamber temperature with exercise, where subjects cycled on a bicycle ergometer at 750 J/min for 20 minutes. Before consuming Cola nitida, participants sat quietly in the sweat chamber for 20 minutes under the respective conditions. Each subject then chewed 0.5 g/kg body weight of Cola nitida as a bolus, followed by drinking 50 ml of deionized water. A 90-minute rest period was observed before re-entering the sweat chamber, where sweat samples were collected using the sweat capsule technique
Keywords: Cola Nitida, Sweat Calcium and Magnesium Concentrations, Sweat Capsule Technique